Social Responsibility and Airbnb Hosts: Voices from Northern Cyprus - BAYRAKTAR, Fetine; REZAPOURAGHDAM, Hamed (Journal of Environmental Management and Tourism; Vol 15 No 2 (2024): JEMT, Volume XV, Issue 2(74), Summer 2024DO - 10.14505/jemt.v15.2(74).07, 2024)
This study examined relevant linkages between motivational factors to be the owner of P2P accommodation (Airbnb host) and being active in pro-environmental and pro-social actions in life practices using a qualitative research method. Our study contributes to the literature associating the motivations of being an Airbnb host and being active in sustainability issues under the framework of moral values. Furthermore, the study analyzed whether an individual awareness of sustainability practices by Airbnb hosts influences their motivations for social responsibility actions in their hosting practices. The key themes followed were ‘Community Engagement and Pro-Social Practices’, ‘Environmental Consciousness and Pro-environmental Practices’, ‘Family Values on Moral Identity and Legal Compliance’, and ‘Restoration and Cultural Heritage’. Findings revealed that hosts stress the importance of the level of environmental consciousness that is gained from education in fostering social responsibility. Respondents believed that teaching cultural heritage, environmental awareness, and ethical values, especially to children, is crucial to building a responsible society. Additionally, participants expressed a sense of social responsibility through the restoration of idle and old houses, contributing to the preservation of cultural heritage and historical structures. As a context of the moral identity issue of respondent hosts, the influence of family values on the development of moral identity was highlighted. The findings of the study showed that hosts work in a team to implement necessary projects for the benefit of society. The study ends with a discussion of the findings and relevant suggestions for the industry.